Training load, sleep, reaction time, sports performance, and mood in paralympic swimmers before a competition - Stieler, E.; Mello, M. T.; Grade, I.; Bernardina, G. R.; Guerreiro, R.; Nascimento, C. D. Silva, A. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Coaches usually reduce the training load (tapering) before competition to improve performance; however, in paralympic athletes this strategy had not yet been tested and we did not know which variables are associated with improved performance. Therefore, the objective was to compare the sleep, mood, sports performance, and reaction time (RT) of paralympic swimmers (PS) during tapering and to investigate whether there is a relationship between the variables during this training phase.